Reduced nocturnal blood pressure dip and sustained nighttime hypertension are specific markers of secondary hypertension - Seeman, Tomás; Palyzová, Daniela; Dusek, Jirí; Janda, Jan (The Journal of pediatrics, 2005)
OBJECTIVE: To investigate with the use of ambulatory blood pressure (BP) monitoring whether nocturnal BP dip and nighttime BP values are different in children with untreated primary and secondary hypertension. STUDY DESIGN: Ambulatory BP monitoring studies from 145 children with untreated hypertension were retrospectively analyzed. Forty-five children had primary hypertension and 100 children had secondary hypertension. RESULTS: Children with secondary hypertension had lower nocturnal BP dip for systolic and diastolic BP in comparison to children with primary hypertension (8% +/- 5% vs 14% +/- 4% for systolic and 14% +/- 7% vs 22% +/- 5% for diastolic BP, P < .0001 for both). Eleven percent of children with primary hypertension were classified as nondipper (BP dip <10%) for systolic BP and no child for diastolic BP; on the contrary, in children with secondary hypertension, 65% were nondippers for systolic and 21% for diastolic BP. Nocturnal systolic and diastolic BP loads were significantly greater in children with secondary hypertension than in those with primary hypertension. CONCLUSIONS: Reduced nocturnal BP dip and sustained nighttime BP elevation are specific markers of secondary hypertension in children with untreated hypertension. Children with blunted nocturnal BP dip or sustained nighttime hypertension should be thoroughly investigated searching for the underlying cause of hypertension.
Keywords: Male; kohortové studie; hypertenze; retrospektivní studie; Cohort Studies; Adolescent; Child; dítě; Adult; Diagnosis, Differential; dospělí; mužské pohlaví; Hypertension; cirkadiánní rytmus; mladiství; Circadian Rhythm; lidé; krevní tlak; ženské pohlaví; Humans; diferenciální diagnóza; senzitivita a specificita; Blood Pressure; ambulantní monitorování krevního tlaku; Sensitivity and Specificity; Retrospective Studies; Blood Pressure Monitoring, Ambulatory; Female